I sell my vote, and so what? : a new database and evidence from Colombia (2017)
Exchanging one's vote for particularistic benefits - practices usually grouped under 'clientelism' - is often thought to weaken programmatic links between citizens and politicians and disincentivize public good provision, as well as undermine voter autonomy and the ideal role of elections. However, empirically analyzing this key phenomenon for the working of democracies entails formidable challenges. We conduct list experiments on a large sample of households to estimate the incidence of clientelistic vote buying, as well as the extent to which respondents refrain from openly recognizing this behavior. Nearly one out of every five respondents engage in clientelism and, surprisingly, they do not feel ashamed to admit it. Using the literature to guide our analysis, we examine the robust correlates of clientelism, finding that vote buying increases with poverty, reciprocity, disregard for the rule of law and, challenging several theories, interest in politics.